Compression Of Acquired Data In Order To Make Transmission And Processing More Efficient - Pintilei, Madalina Ancuta; Ursu, Ileana; Pascu, Sebastian; Schreiner, Cristina Mihaela; Aradoaei, Mihaela; Olteanu, Alin (International Conference and Exposition on Electrical and Power Engineering (Online), 2022)
The article below briefly presents the subject of lossy compression for various types of sensor acquired data. The type and amount of data from the transmission line sensor network will be analyzed, the data compression algorithms will be compared, and a proposed efficient lossy compression algorithm suitable for transmission line data will be favored. It presents what is currently in use on the market.